Academic Trends of Paper Press in Comparison with Internet Press A Field Study on Professors o College of Media at University of Baghdad - Hadi Saleh, Rawa (ALBAHITH ALALAMI, 2019)
This search seeks to know the trends of academics in the field of Press and audio, video and read press about paper press compared with continued development and widespread deployment of web journalism. This research belongs to descriptive studies which depends on sample survey approach adopted by five-meter design measuring trends. It contains 28 items having applied honesty and reliability transaction and the scale form is distributed to the sample studied of about 110 professors and then the researcher collects them and then applying the appropriate statistical program to get the results. This search seeks to know the trends of academics in the field of Press and audio, video and read press about paper press compared with continued development and widespread deployment of web journalism. This research belongs to descriptive studies which depends on sample survey approach adopted by five-meter design measuring trends. It contains 28 items having applied honesty and reliability transaction and the scale form is distributed to the sample studied of about 110 professors and then the researcher collects them and then applying the appropriate statistical program to get the results. We reach to the following results: 1-The sample of professors have a positive trend towards online journalism. 2-Gender does not affect the trends of respondents and there are no clear differences depending on the university, specialization and certificate variables 3-There are statistical differences in trends of academics specializing in media towards online journalism for radio and T.V 4-Paper press no longer responsive and saturate to the needs of respondents. 5-All of the respondents do not prefer paper press due to lack of immediate, interactive and multimedia prosperity